Exploration of Sequence-wise Optimized Parameters for Low Complexity Enhancement Video Coding (LCEVC) on 4K Content - Benjak, Martin; Ostermann, Jorn (Proceedings of the ... IEEE International Conference on Acoustics, Speech and Signal Processing (1998), 2025)
This paper explores the configuration space of Low Complexity Enhancement Video Coding (LCEVC) for 4K SDR content and the VVC reference software VTM as base layer codec. The configuration space is spanned using a sweep over multiple values for the base layer QP and the LCEVC parameters sublayer 2 step width, scaling mode, number of processed picture planes, transformation type, and sequence-wise optimized upscaling filter coefficients. The best configurations are selected using a convex hull approach. Compared to the default LCEVC configuration, we achieve average BD-rate gains of 10.92% and 2.06% using 1d and 2d upscaling, respectively. However, our best possible LCEVC configuration still yields an average YCbCr BD-rate loss of 15.26% compared to VTM at full resolution.